ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 99K/TUN/2020 TENTANG SENGKETA TERBITNYA SERTIPIKAT TANAH ANTARA PEMERINTAH PROVINSI DKI JAKARTA MELAWAN PT. BUANA PERMATA HIJAU - Matthew Sebastian; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Land is closely related to humans. This creates conflict in society. Especially regarding arable rights whose rules are not yet clear. Often disputes occur between civil society and government officials, especially regarding land used for development in the public interest. The author wants to know what are the legal considerations of the Supreme Court in the decision number 99K/TUN/2020 which strengthens the usufructuary rights number 314/315 belonging to the DKI Jakarta Provincial government, by analyzing the validity of the land certificate belonging to the DKI Jakarta Provincial Government in this case, with the applicable rules. The research method used is normative research. Based on the author's analysis, there are several things that make the judges should not ignore the arable rights of PT Buana Permata Hijau. Some of these things are that the SK on price estimation which is used as the basis for the consignment has expired. Then the consignment made is not in accordance with the applicable regulations. In addition, the handover by PT Agung Podomoro to the DKI Jakarta Provincial Government was not in accordance with the applicable regulations. This is used as the basis for the issuance of a certificate of use rights of the DKI Provincial Government. Therefore, it can be concluded that the certificate of use rights of the DKI Provincial Government is not appropriate to be issued by the National Land Agency because the land is still in a state of dispute.